The Relationship between Dialysis Metrics and Patient-Reported Cognition, Fatigue, and Physical Function - Daniel A. Sturgill; Naveet Bal; Sneha Nagavally; Dawn F. Wolfgram (Karger Publishers, 2020)
Introduction: The impact of achieving hemodialysis laboratory and hemodynamic quality metrics on patient-reported outcomes (PROs) is unknown. Objective: To determine if meeting dialysis laboratory quality of care measures is associated with improved PROs. Methods: In this cross-sectional study, we measured the relationship between dialysis patients' Patient Reported Outcome Measurement Information System (PROMIS) scores and commonly used dialysis quality of care measures. Results: PROMIS surveys were administered to 92 dialysis patients. The mean ± SD scores demonstrated higher fatigue (55.0 ± 9.8) and lower physical function (37.9 ± 7.9) but similar cognition (50.3 ± 10.9) compared to general population normative scores of 50 ± 10. Dialysis patients meeting Kt/V goals had no better scores than those who did not. Meeting the hemoglobin (Hgb) value of ≥10 g/dL was associated with a lower fatigue score, but no difference in cognitive or physical function scores. Meeting the serum albumin goal of ≥4.0 mg/dL was associated with a higher physical function score but made no difference for cognitive function or fatigue score. As a continuous variable, a higher Hgb was associated with lower reported fatigue (HR −1.74 95%, CI [−3.09, −0.39]), but no other measures were associated with PRO scores when adjusted for demographics and comorbidities. Conclusions: We found little association between measures currently used to assess the quality of dialysis care and PROs. Encouraging improved utilization of PROs and incorporating PROs into quality measurements might give a more robust assessment of quality of care. Future studies should assess the benefits of this approach.